(untitled) (The Strategic Review for Southern Africa, 2021)
With both leaders focused on integration (or re-integration) with their respective regions, between South Africa and Russia under the coinciding presidencies of Thabo Mbeki and Vladimir Putin (1999 to 2008) distal ties would appear to have been a peripheral consideration, albeit one pursued with relative consistency. These years were un-ideological, having followed the collapse of the USSR but preceding the emergence of the intermittently ideological BRICS project. I use trade data from multiple sources to assess the two countries' economic relationship under these leaders. Upon noting the continued but slow growth in political interaction under the two leaders, the article documents the effects of political interaction on trade, which was encouraged by both leaders as they sought deeper south-south cooperation (SSC) and lessened dependency on the West (with which both countries were nevertheless growingly intertwined). Trade responded favourably on both sides after the 2006 mutual visits by the two presidents (as seen by 2007 trade volumes). Overall, under the Mbeki-Putin years, we observe Russian products forming a higher share of South African imports than the other way around, whilst growth in access to each other's markets saw mostly new access for South Africa (giving it a favourable surplus of over US25-million, which grew to over US2-billion under the Zuma years), thereby complicating our understanding of the relationship and the nature of the asymmetry which defines it.